MEMBANGUN KARAKTER SISWA BERBASIS TASAWUF DI MI KHALAFIYAH SYAFI’IYAH ZAINUL HASAN GENGGONG - Ubudiyah, Azizah Aziziyah; Bukhori, Imam; Wagianto, Ramdan (Jurnal Al-Fatih, 2025)
Education not only aims to educate, but also to form moral and spiritual character. In the modern era, the challenge of maintaining Islamic values is increasingly greater due to the influence of materialistic and individualistic culture. The implementation of Sufism values in the madrasah environment can be carried out in various ways, such as thematic learning based on spiritual values, habituation of noble morals in daily activities, and examples provided by educators. This study examines the application of Sufism values in building the character of students at MI Khalafiyah Syafi'iyah Zainul Hasan Genggong. With qualitative methods and field research, data was collected through observation, interviews, and literature studies. The results of the study show that the integration of Sufism is carried out through the habituation of noble morals, the example of teachers, and spiritual activities such as dhikr and moral studies. By internalizing the values of Sufism, students are taught to respect morality and ethics, as well as developing a closer relationship with God, so that they grow into responsible and virtuous individuals. This approach has proven to be effective in forming students who are not only academically superior, but also have Islamic morals.